Peningkatan Kapasitas Sel Pada Sistem Seluler GSM - Alfin Hikmaturokhman; Hesti Susilawati; Shinta Yunita Sari (JURNAL INFOTEL, 2009)
Increasing cell capacity in GSM applied by several methods such as Fixed Channel Allocation (FCA), Channel Sharing, Channel Borrowing and Cell Splitting to solve the massive increasing of cellular users amount in the whole world. It necessary to calculate the number of the subscriber within each cell in a certain busy hour based on available channel capacity in order to serve the traffic capacity in a cell. In this work, we present calculations to compare cell capacity without increasing cell capacity method and cell capacity using increasing capacity methods. As a programming tool, we used Borland Delphi 7. In addition, this simulation software added with comprehensive explanations, Erlang B Table, and graphics to make it easier and more efficient in analyzing.